Islamic Economic Perspectives on Wage Systems in The Furniture Business: : Case Study on the Furniture Business of Tahfidzul Qur'an Boarding School, Sidorejo, Pagelaran, Malang - Alfiyatus Sa’adah; Ririn Noviyanti (Iqtishodia: Jurnal Ekonomi Syariah, 2021)
This study aims to conduct an in-depth analysis of the remuneration system for the furniture of the Tahfidzil Qur'an Islamic Boarding School (PPTQ) in Sidorejo Village, Pagelaran District, Malang Regency, from a sharia economic perspective (Case Study). This research is descriptive qualitative using primary and secondary data sources. Methods of data collection using interviews, observations and documents. The focus of this research is on the remuneration system for furniture workers located in the Tahfidzil Qur'an Islamic Boarding School in Sidorejo based on the perspective of Islamic Economics. The results of the study indicate that the wage system has complied with several aspects of sharia, namely: the amount of wages given to workers in accordance with the mutually agreed contract at the beginning. Second, wages are given on time according to a predetermined time. Third, the wages given are included as appropriate to be given to workers because they have met the daily needs of the workers. Fourth, the wages given to workers are not the same depending on the work done while working.